After Corporate Paternalism Material Renovation and Social Change in the Time of Ruination (Volume 24) - Straube, Christian (Berghahn Books, 2021)
In this ethnographic study of post-paternalist ruination and renovation, Christian Straube explores social change at the intersection of material decay and social disconnection in the former mine township Mpatamatu of Luanshya, one of the oldest mining towns on the Zambian Copperbelt. Touching on topics including industrial history, colonial town planning, social control and materiality, gender relations and neoliberal structural change, After Corporate Paternalism offers unique insights into how people reappropriate former corporate spaces and transform them into personal projects of renovation, fundamentally changing the characteristics of their community.